Development, characterization and evaluation of raloxifene nanoemulgel for topical delivery - Ali, Ebrahim Mohammed Hasan (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2018)
Raloxifene is a second-generation selective oestrogen receptor modulator (SERM) used in treatment of osteoporosis in postmenopausal women as well as in the prevention of invasive breast cancer. This drug has a poor bioavailability, which is limited to only 2%. The aim of this study was to develop, characterize and evaluate of raloxifene nanoemulgel for topical delivery. Four nanoemulsion formulations (NE13, NE14, NE15 and NE16), containing sunflower oil as oil phase, distilled water, Tween 20 as surfactant and Transcutol as co-surfactant were prepared at different ratios. The nanoemulsion formulations were prepared by using a sonicator. The formulations were characterized such as pH, transmittance, refractive index, viscosity, particle size, zeta potential, thermodynamic stability and morphology structure (TEM). NE15 was selected as the most stable formulation that did not show any phase separation, which passed the thermodynamic stability. In addition, it had a high transmittance (%T) at 98.4%, refractive index at 1.38, zeta potential value at 33.80±1.35 mV with a low particle size at 153.10± 4.47 nm and polydispersion index of 0.259±0.03. The viscosity of NE15 was recorded at 12.80±0.33. The TEM image showed that, nanoemulsion globules less than 200 nm, which agreement with the result in nano size range that obtained by the Malvern Zetasizer. The optimized nanoemulsion was incorporated into different ratio of gel Carbopol® 940 3% (gelling agent) to fabricate nanoemulgel (NG1, NG2, NG3, NG4 and NG5). The nanoemulgel formulations were subjected for different evaluations, namely, stability study, drug content, texture analysis (hardness and cohesiveness), rheological properties, spreadability, assessment of local toxicity on rat skin and permeation study using abdominal skin rat. The permeation of raloxifene from nanoemulgel was measured using Frenz diffusion cell and the data were analysed by HPLC. The ex-vivo permeation of nanoemulgel formulations were compared with the suspension raloxifene (control). NG3 was selected as the best formulation as it has the highest drug loading at 99.07 %±1.25 with a higher maximum cumulative release at 76.72 (µg/cm2) and flux (J) was found to be at 11.84 µg/cm2/h. The drug release of the nanoemulgel formulations were found to be higher than suspension (control). The rheological properties exhibited that, the formulation has a viscoelastic behaviour. The viscosity, hardness and cohesiveness of NG3 recorded at 60.13±10 Pas, 94.0±4.62 g and -0.26±0.05 respectively. The result of the assessment of local toxicity on skin showed that, the skin structure remained intact after applying nanoemulgel. The stability study of nanoemulgel (NG3) was done for one month at room temperature to evaluate drug content (drug degradation) and physical changes such as colour, pH and separation phase. Only 1 % of the drug in nanoemulgel formulation was degraded after one month. There was no physical change in the formulation. Hence, it can be concluded that, nanoemulgel formulation is a suitable and safe for application as a topical delivery of raloxifene.